Análisis de los parámetros eléctricos de la red subterránea de distribución a 13.8kva., lo que permitirá encontrar puntos críticos del alimentador doce de noviembre del cantón Ambato, año 2015 - Valle Villacres, Jorge H. (2016)
It is the great importance for Electric Company Ambato Regional Centro Norte SA (EEASA) it provides the consumer a high quality electric service of the technical service product which on have established leaves by law, with this study it look for increasing the level of reliability and reduce the probability that there is defect in the underground distribution network system that feeds the center of the Ambato city....